DESCRIPTIVE STUDY OF STUDENT"™S UNDERSTANDING OF MICROSCOPES AT SMAN 1 KUBU IN KUBU RAYA REGENCY - Fitriani, Eria; Candramila, Wolly; Mardiyyaningsih, Asriah Nurdini (EduNaturalia: Jurnal Biologi dan Kependidikan Biologi, 2025)
Biology education at the secondary school level adopts a scientific approach that emphasizes critical, analytical, and selective thinking skills. Practicum activities, particularly microscope use, are essential components in developing students"™ technical and analytical abilities. However, laboratory utilization at SMA Negeri 1 Kubu has not been optimal. This study aims to describe students"™ knowledge of microscopes and their usage as a basis for improving learning strategies and laboratory management. A descriptive qualitative method was employed using a questionnaire covering four main aspects: the name of the microscope, its function, its components, and how to operate it. The results showed that while all students could correctly identify the name of the microscope, their understanding of its function, components, and operation remained limited. Therefore, it is recommended that teachers increase the frequency of practicum sessions, provide more structured guidance, and apply experiential learning approaches. The implications of this study indicate that enhancing students"™ understanding of microscope use requires effective laboratory management and the implementation of more active and systematic learning strategies to improve students"™ practical competencies and biology learning outcomes. Keywords: Biology Education, Microscope, Practicum, Laboratory, Learning Strategy